FINGER RECONGITION AND GESTURE BASED VIRTUAL KEYBOARD (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Hand gesture recognition is very significant for human-computer interaction.In this work, we present a novel real-time method for hand gesture recognition. The proposedsystem is vision based, which uses machine learning techniques and inputs from a computerwebcam. Vision based gesture recognition tracking and gesture recognition in our framework,the hand region is extracted from the background with the background subtraction method.Finally, a rule classifier is applied to predict the labels of hand gestures. Our method showsbetter performance than a state-of-art method on another data set of hand gestures